2016
DOI: 10.1158/1535-7163.mct-16-0142
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Inhibition of EGFR: Modeling the Combined Pharmacokinetic–Pharmacodynamic Relationship of Osimertinib and Its Active Metabolite AZ5104

Abstract: Osimertinib (AZD9291) is a potent, selective, irreversible inhibitor of EGFR-sensitizing (exon 19 and L858R) and T790M-resistant mutation. In vivo, in the mouse, it is metabolized to an active des-methyl metabolite, AZ5104. To understand the therapeutic potential in patients, this study aimed to assess the relationship between osimertinib pharmacokinetics, the pharmacokinetics of the active metabolite, the pharmacodynamics of phosphorylated EGFR reduction, and efficacy in mouse xenograft models of EGFR-driven … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
2
33
1
Order By: Relevance
“…The activity of AZD3759 in brain was evaluated by detecting the extent and duration of pEGFR reduction relative to the free concentration of AZD3759 in brain …”
Section: Methodsmentioning
confidence: 99%
“…The activity of AZD3759 in brain was evaluated by detecting the extent and duration of pEGFR reduction relative to the free concentration of AZD3759 in brain …”
Section: Methodsmentioning
confidence: 99%
“…A series of modeling studies was undertaken to predict active doses of osimertinib in humans by incorporating human PK data into a previously developed PK-pharmacodynamic (PKPD) PC9 subcutaneous xenograft efficacy model that linked phosphorylated EGFR (pEGFR) inhibition to reductions in tumor volume (34). The studies also accounted for reduced free concentrations in the brain due to higher levels of binding than observed in plasma.…”
Section: Pharmacokinetic-pharmacodynamic Modelingmentioning
confidence: 99%
“…Although several simultaneous pharmacokinetic studies of osimertinib, AZ5104 and AZ7750 were reported in papers, as well as the quantification methods for simultaneous determination of osimertinib and its active metabolites (Brown et al, ; Planchard et al, ; Yates et al, ; Zhao et al, ), details of these assays were, other than the use of protein precipitation, electrospray ionization and a labeled compound as internal standard (IS), never reported. Recently, a method reported by Vishwanathan et al () showed that the accuracy ranged from 93.5 to 123.7%, which was not suitable for PK studies.…”
Section: Introductionmentioning
confidence: 99%